Adenovirus serotype 5 vectors with Tat-PTD modified hexon and serotype 35 fiber show greatly enhanced transduction capacity of primary cell cultures. - Di Yu; Chuan Jin; Mohanraj Ramachandran; Jing Xu; Berith Nilsson; Olle Korsgren; Katarina Le Blanc; Lene Uhrbom; Karin Forsberg-Nilsson; Bengt Westermark; Rachel Adamson; Norman Maitland; et al. (PLoS ONE)
Recombinant adenovirus serotype 5 (Ad5) vectors represent one of the most efficient gene delivery vectors in life sciences. However, Ad5 is dependent on expression of the coxsackievirus-adenovirus-receptor (CAR) on the surface of target cell for efficient transduction, which limits it's utility for certain cell types. Herein we present a new vector, Ad5PTDf35, which is an Ad5 vector having serotype 35 fiber-specificity and Tat-PTD hexon-modification. This vector shows dramatically increased transduction capacity of primary human cell cultures including T cells, monocytes, macrophages, dendritic cells, pancreatic islets and exocrine cells, mesenchymal stem cells and tumor initiating cells. Biodistribution in mice following systemic administration (tail-vein injection) show significantly reduced uptake in the liver and spleen of Ad5PTDf35 compared to unmodified Ad5. Therefore, replication-competent viruses with these modifications may be further developed as oncolytic agents for cancer therapy. User-friendly backbone plasmids containing these modifications were developed for compatibility to the AdEasy-system to facilitate the development of surface-modified adenoviruses for gene delivery to difficult-to-transduce cells in basic, pre-clinical and clinical research.